Application of Tilapia Cultivation Biofloc Technology For Utilization of Non-Productive House Yards - Dewi Hikmah Marisda; Anisa (Pusat Publikasi ITS, 2019)
The community partnership program, titled Tilapia fish cultivation with Bioflock technology, was carried out in Gowa Regency in the Juluatia farmer group chaired by Ms. Kasmawati, aimed at empowering farmer groups to become productive entrepreneurs. This activity has short-term programs, namely: 1) Optimizing unproductive home yards; 2) Improve the knowledge and skills of tilapia farming. This activity program is carried out for 8 (eight) months with 1 (one) The Community Partnership Program partner. The stages of the community partnership program implementation include the stage of surney preparation and site review, analysis of potential and problem partners, and implementation of PKM activities. The technology applied in this PKM activity is Bioflock technology in aquaculture minimize the use of artificial feed, as well as the efficient use of water. From the results of the implementation of this PKM produced 3 (three) units of Bioflock tilapia ponds, increasing science and technology in the community, especially in the Juluatia farmer group.